Inclusive Digital Technology for People with Communication Disabilities in Indonesia (Universitas Terbuka, 2025)
The global digital transformation offers significant opportunities to enhance the quality of life for persons with disabilities, especially those with communication impairments. Access to digital technology should not be viewed merely as a technical matter but as a fundamental human right. In Indonesia, several legal frameworks, including Law No. 8 of 2016 on Persons with Disabilities and Government Regulations No. 13/2020 and No. 70/2019, emphasize reasonable accommodation, accessibility, and the national disability roadmap. Collaborative efforts from government, private sector, and civil society—such as inclusive digital literacy programs, development of adaptive applications, and community-driven innovations—reflect promising progress. Nevertheless, substantial challenges remain, including unequal access to internet and devices, low levels of digital literacy among marginalized groups, and limited implementation of international accessibility standards such as WCAG. Addressing these gaps requires stronger policy enforcement, cross-sector partnerships, and inclusive design approaches. This paper explores policies, practices, challenges, and opportunities for advancing inclusive digital technologies in Indonesia, with particular attention to communication disabilities.